MODELLING OF ISLAMIC SPIRITUALITY (MUROQOBAH) AND PRO-ENVIRONMENTAL BEHAVIOR: A FACTOR ANALYSIS APPROACH. - Ernawati Ernawati; Dinda Minkhatul Maula (KNOWLEDGE: Jurnal Inovasi Hasil Penelitian dan Pengembangan, 2026)
Environmental degradation is not only an ecological issue but also a moral and spiritual challenge, highlighting the need to examine internal psychological factors that support sustainable behavior. This study aimed to validate muraqabah as an Islamic spirituality-based self-regulation construct and to test its effect on pro-environmental behavior (PEB) among Muslim university students. Using a quantitative design, the study employed item discrimination analysis, Exploratory Factor Analysis (EFA), Confirmatory Factor Analysis (CFA), and Structural Equation Modeling (SEM). Data were collected from two independent samples, comprising 105 participants in the exploratory phase and 200 participants in the confirmatory and structural phases. The findings supported the multidimensional structure of the Muraqabah Scale and showed that muraqabah had a significant positive effect on PEB (β = 0.605, p < .001). These results indicate that muraqabah strengthens moral responsibility, self-regulation, and intrinsic motivation for environmentally responsible behavior. This study offers both a psychometric contribution, by validating muraqabah as a measurable construct, and a substantive contribution, by demonstrating its role as a spiritual predictor of PEB in an Islamic higher education context. The study is limited by its cross-sectional design, self-report measures, and restricted institutional sample; future research should therefore involve more diverse populations and longitudinal designs. ABSTRAK Kerusakan lingkungan bukan hanya merupakan persoalan ekologis, tetapi juga tantangan moral dan spiritual, sehingga penting untuk mengkaji faktor-faktor psikologis internal yang mendukung perilaku berkelanjutan. Penelitian ini bertujuan untuk memvalidasi muraqabah sebagai konstruk regulasi diri berbasis spiritualitas Islam serta menguji pengaruhnya terhadap perilaku pro-lingkungan (pro-environmental behavior/PEB) pada mahasiswa Muslim. Dengan menggunakan desain kuantitatif, penelitian ini menerapkan analisis daya beda item, Exploratory Factor Analysis (EFA), Confirmatory Factor Analysis (CFA), dan Structural Equation Modeling (SEM). Data dikumpulkan dari dua sampel independen, yaitu 105 partisipan pada tahap eksploratori dan 200 partisipan pada tahap konfirmatori serta struktural. Hasil penelitian mendukung struktur multidimensi Skala Muraqabah dan menunjukkan bahwa muraqabah berpengaruh positif signifikan terhadap PEB (β = 0,605; p < 0,001). Temuan ini menunjukkan bahwa muraqabah memperkuat tanggung jawab moral, regulasi diri, dan motivasi intrinsik untuk berperilaku ramah lingkungan. Penelitian ini memberikan kontribusi psikometrik melalui validasi muraqabah sebagai konstruk yang dapat diukur, sekaligus kontribusi substantif dengan menunjukkan perannya sebagai prediktor spiritual perilaku pro-lingkungan dalam konteks pendidikan tinggi Islam. Penelitian ini memiliki keterbatasan pada desain potong lintang, penggunaan instrumen laporan diri, dan cakupan sampel yang terbatas pada institusi tertentu; oleh karena itu, penelitian selanjutnya perlu melibatkan populasi yang lebih beragam dan menggunakan desain longitudinal.